Pengaruh Social Support, Service Security, Information Quality, Perceived Ease To Use, Perceived Usefulness terhadap Trust dan Repurchase Intention pada Pengguna Aplikasi Shopee : Studi pada Mahasiswa Unissula - Indah Khumalasari; Hendar Hendar (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to evaluate the impact of social support, service security guarantees, information quality, perception of operational ease, and perception of usefulness in forming trust and the tendency to make repurchases by Shopee application users. The main focus of this study is to assess how the role of support from the social environment, perception of transaction security, reliability of the information provided, ease of use, and usability of applications in forming trust, ultimately drives users' decisions to return to purchase. This research was conducted on students of the Sultan Agung Islamic University (UNISSULA) in Semarang, with a quantitative approach and an explanatory research design. A total of 200 respondents were selected selectively using the purposive sampling technique. Data was obtained through the distribution of closed questionnaires that have been tested for validity and reliability. Data analysis was carried out using multiple linear regression methods and path analysis to test the role of trust mediation as an intervening variable that affects the relationship between free variables and repurchase intentions. The results show that social support, service security, information quality, ease of use, and usability of applications have a significant influence on user trust. This trust then proved to be a strong mediating variable in influencing the repurchase intention of Shopee users. These findings confirm the importance of psychological and functional aspects in building customer loyalty on digital-based and ever-evolving e-commerce platforms. The practical implications of this study encourage e-commerce players to focus on improving the quality of digital services by paying attention to user perceptions of convenience, usability, and security, as well as strengthening social communication that builds trust.